Evaluation of the antineoplastic activity of gallic acid in oral squamous cell carcinoma under hypoxic conditions. Issue 5 (June 2016) - Guimaraes, Talita A.; Farias, Lucyana C.; Fraga, Carlos A.; Feltenberger, John D.; Melo, Geraldo A.; Coletta, Ricardo D.; Souza Santos, Sergio H.; de Paula, Alfredo M.B.; Guimaraes, Andre L.
Abstract : The purpose of the current study was to develop and test a theoretical model that could explain the mechanism of action of gallic acid (GA) in the oral squamous cell carcinoma context for the first time. The theoretical model was developed using bioinformatics and interaction network analysis to evaluate the effect of GA on oral squamous cell carcinoma. In a second step to confirm theoretical results, migration, invasion, proliferation, and gene expression (Col1A1, E-cadherin, HIF-1α, and caspase-3) were performed under normoxic and hypoxic conditions. Our study indicated that treatment with GA resulted in the inhibition of cell proliferation, migration, and invasion in neoplastic cells. Observation of the molecular mechanism showed that GA upregulates E-cadherin expression and downregulates Col1A1 and HIF-1α expression, suggesting that GA might be a potential anticancer compound. In conclusion, the present study demonstrated that GA significantly reduces cell proliferation, invasion, and migration by increasing E-cadherin and repressing Col1A1. Abstract : Supplemental Digital Content is available in the text.